On the origin of mesopore collapse in functionalized porous carbons. (August 2019) - Zhang, En; Casco, Mirian Elizabeth; Xu, Fei; Sheng, Wen-Bo; Oswald, Steffen; Giebeler, Lars; Wegner, Karl; Borchardt, Lars; Kaskel, Stefan
Abstract: Heteroatom functionalization of ordered mesoporous carbon (OMC) represents an important strategy towards electrocatalytic and battery applications. Such functionalization frequently leads to degradation or even collapse of mesopores, which is generally attributed to the harsh conditions used or the successfully doped functional groups or the entrapment of guest species into mesopores. However, in this report, we find the structural deterioration of functionalized OMC is mainly induced by the water evaporation during the drying process, beyond the usually accepted concept mentioned above. We report two types of well-defined OMCs, resembling comparable pore architectures but varying in surface chemistry, namely the hydrophobic OMC (Cmeso ) and hydrophilic one (HCmeso ). After washing and drying processes, Cmeso remains intact regardless of the drying processes. In sharp contrast, HCmeso shows gradual porosity deterioration or even totally collapse under continuous washing-drying cycles. Lyophilization can however well preserve the porosity due to the reduced stress exerted by water on carbon walls. Such a distinct phenomenon is elaborately characterized by N2 physisorption, H2 O physisorption, TEM and SAXS and further validated by well-known CMK-3, which undergoes surface functionalization by concentrated HNO3 . Our finding reveals an important but neglected issue addressing the drying process in particular for polar functionalized porous carbons. Graphical abstract: Image 1